Alteration of the DNA Methylation Signature of Renal Erythropoietin-Producing Cells Governs the Sensitivity to Drugs Targeting the Hypoxia-Response Pathway in Kidney Disease Progression - Sato, Koji; Kumagai, Naonori; Suzuki, Norio (Frontiers in Genetics, 2019)
Chronic kidney disease (CKD) affects more than 10% of the population worldwide and burdens citizens with heavy medical expenses in many countries. Because a vital erythroid growth factor, erythropoietin (EPO), is secreted from renal interstitial fibroblasts (renal EPO-producing [REP] cells), anemia arises as a major complication of CKD. We determined that hypoxia-inducible factor 2 (HIF2), which is inactivated by HIF-prolyl hydroxylase domain-containing proteins (PHDs) in an oxygen-dependent manner, tightly regulates EPO production in REP cells at the gene transcription level to maintain oxygen homeostasis. HIF2-mediated disassembly of the nucleosome in the EPO gene is also involved in hypoxia-inducible EPO production. In renal anemia patients, anemic and pathological hypoxia is ineffective toward EPO induction due to the inappropriate over-activation of PHDs in REP cells transformed into myofibroblasts (MF-REP cells) due to kidney damage. Accordingly, PHD inhibitory compounds are being developed for the treatment of renal anemia. However, our studies have demonstrated that the promoter regions of the genes encoding EPO and HIF2 are highly methylated in MF-REP cells, and the expression of these genes is epigenetically silenced with CKD progression. This finding notably indicates that the efficacy of PHD inhibitors depends on the CKD stage of each patient. In addition, a strategy for harvesting renal cells, including REP cells from the urine of patients, is proposed to identify plausible biomarkers for CKD and to develop personalized precision medicine against CKD by a non-invasive strategy.